Analysis of Length of Stay (LOS) of Diabetes Mellitus Patients with COVID-19 Confirmed at One of Bantul Private Hospitals - Masfiyah, Lukluul; Estiningsih, Daru; Astuti, Witri Susila; Hadi, Ninisita Sri (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Diabetes mellitus (DM) is one of the most common health problems affecting millions of people in the world. Based on data from the Indonesian COVID-19 Handling Task Force, as of May 2021, it is known that the prevalence of DM as a comorbid COVID-19 is 33.6%. The variety of clinical conditions that accompany DM cases makes the complexity of patient care increase, which results in variations in patient LOS as one of the quality indicators to support better management and to improve the quality of service for DM patients confirmed with COVID-19 and not confirmed COVID-19. The purpose of this study was to determine whether or not there is a difference in the Length of Stay (LOS) of DM patients confirmed with COVID-19 and not confirmed with COVID-19 with the type of observational analytic cross-sectional design. Result Research shows that based on the Mann-Whitney test used to determine the difference in length of stay between DM patients confirmed with COVID-19 and not confirmed COVID-19, they get significant results, namely p-value = 0.000 (p<0.050). It can be concluded that there is a difference between the Length Of Stay (LOS) of Diabetes Miletus patients confirmed with COVID-19 and diabetes mellitus patients who are not confirmed with COVID-19.